Analysis of the agricultural development model and the transformation that occurred in Dagen Village, Jaten Subdistrict, Karanganyar Regency - Aisiyah, Liliyes Lina Tory; Luthfi, Raihan Andhika; Sampurani, Salsabila; Fitriyyah, Sofia; Lopulalan, Reinhard Richard; Antriyandarti, Ernoiz (Institute for Advanced Science, Social, and Sustainable Future, 2024)
This research aims to explain the potential and problems in Dagen Village, structural and institutional transformation, technology transfer, as well as analysis of appropriate agricultural development models to be implemented in the village. Methods: Methodologically, this research consists of data collection and data analysis. Data collection was carried out by observation, interviews, recording and documentation. Meanwhile, the analysis was carried out using qualitative research methods. Results: The results of this research found several findings. First, the potential of Dagen Village lies in rice farming land, while the problem of Dagen Village is factory waste pollution due to industrial activities which can threaten the sustainability and productivity of the land. Second, the structural transformation that occurred was a gradual transition from agricultural activities to the non-agricultural sector, then from the industrial sector to the service sector. Third, institutional transformation occurs gradually, starting from habits, becoming culture, from the perspective of Poktan and Gapoktan it can be said to be empowered, described by the ownership of assets, mastery of science and technology, as well as freedom in making choices and decisions in agribusiness activities in rural areas. Fourth, technology transfer is channeled by various contributory parties. Fifth, the Agricultural Development model in Degan Village uses the Locational Mode model based on Von Thunen's theory that differences in transportation of each agricultural commodity from the place of production to the nearest market influence the type of land use in an area.